Incidence, prevalence and clinical correlates of antidepressant‐emergent mania in bipolar depression: a systematic review and meta‐analysis. (14th February 2018) - Fornaro, Michele; Anastasia, Annalisa; Novello, Stefano; Fusco, Andrea; Solmi, Marco; Monaco, Francesco; Veronese, Nicola; De Berardis, Domenico; de Bartolomeis, Andrea
Abstract : Background: Treatment‐emergent mania (TEM) represents a common phenomenon inconsistently reported across primary studies, warranting further assessment. Methods: A systematic review and meta‐analysis following the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) and Meta‐Analysis of Observational Studies in Epidemiology (MOOSE) guidelines were conducted. Major electronic databases were searched from inception to May 2017 to assess the incidence and prevalence rates and clinical features associated with manic switch among bipolar depressed patients receiving antidepressants, using meta‐regression and subgroup analysis. Results: Overall, 10 098 depressed patients with bipolar disorder (BD) across 51 studies/arms were included in the quantitative analysis. The cumulative incidence of cases (TEM + ) among 4767 patients with BD over 15 retrospective studies was 30.9% (95% confidence interval [CI] 19.6‐45.0%, I 2 = 97.9%). The cumulative incidence of TEM + among 1929 patients with BD over 12 prospective open studies was 14.4% (95% CI 7.4‐26.1%, I 2 = 93.7%). The cumulative incidence of TEM + among 1316 patients with BD over 20 randomized controlled trials (RCTs) was 11.8% (95% CI 8.4‐16.34%, I 2 = 73.46%). The pooled prevalence of TEM + among 2086 patients with BD over four cross‐sectional studies was 30.9% (95% CI 18.1‐47.4%, I 2 = 95.6%). Overall, concurrent lithium therapy predicted the lowest TEM rates. Inconsistent operational definitions of TEM were recorded, and the lack of information about age, sex, co‐occurring anxiety, and other clinically relevant moderators precluded further stratification of the results. Conclusions: Rates of TEM vary primarily depending on study setting, which is concordant with the high degree of heterogeneity of the included records. Forthcoming RCT studies should adopt consistent operational definitions of TEM and broaden the number of moderators, in order to contribute most effectively to the identification of clear‐cut sub‐phenotypes of BD and patient‐tailored pharmacotherapy.